2021
DOI: 10.1371/journal.pone.0250942
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiplex real-time RT-PCR assay for the detection of SARS-CoV-2

Abstract: The outbreak of the new human coronavirus SARS-CoV-2 (also known as 2019-nCoV) continues to increase globally. The real-time reverse transcription polymerase chain reaction (rRT-PCR) is the most used technique in virus detection. However, possible false-negative and false-positive results produce misleading consequences, making it necessary to improve existing methods. Here, we developed a multiplex rRT-PCR diagnostic method, which targets two viral genes (RdRP and E) and one human gene (RP) simultaneously. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…RT-PCR tests have been developed to target RdRP , E , N , or S genes 10 , 21 , 22 . Among these, those targeting RdRP gene were found to be the ones with the highest analytical sensitivity 9 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR tests have been developed to target RdRP , E , N , or S genes 10 , 21 , 22 . Among these, those targeting RdRP gene were found to be the ones with the highest analytical sensitivity 9 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the sex distribution was almost balanced. Previous studies also showed no substantial difference between genders, 51% boys in Italy until July 21, 2020 [ 11 ], 57% in the United States [ 21 ], and 56.6% boys in China [ 9 ]. In another study on Iranian children by Soltani et al [ 19 ], 46.7% of the evaluated 30 children were male [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…RNAseP gene was used as an internal control. All runs were performed using the RT-PCR device (Rotor gene Q, QIAGEN, Germany) according to the kit instructions [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“… 30 Nuclear acid sequence-based amplification (NASBA), restriction enzyme analysis (REA), direct immunofluorescence assay (IFA), enzyme-linked immunosorbent assay (ELISA), and reverse transcription polymerase chain reaction (RT-PCR) are among the most frequently used methods for virus detection. 31 Multiple PCR can simultaneously amplify several nucleic acid targets in a single sample. The standard method for the detection of PCR products, agarose gel electrophoresis, is usually combined with Southern blot to determine sequence specificity.…”
Section: Current Methods For the Detection Of Sars-cov-2 And Its Mutantsmentioning
confidence: 99%